Multislice computed tomography urography in the diagnosis of urinary tract diseases - Nikolić Olivera; Stojanović Sanja; Till Viktor; Basta-Nikolić Marijana; Petrović Kosta; Vučaj-Ćirilović Viktorija (Vojnosanitetski Pregled)
Background/Aim. Multislice computed tomography (MSCT) has triggered considerable changes in uroradiological imaging. The aim of this study was to establish the place of MSCT urography (MSCTU) in comparison with intravenous urography (IVU) and to determine the sensitivity and specificity of MSCT in the evaluation of urothelial abnormalities. Methods. This prospective study included 120 patients with a high clinical suspicion of urinary tract diseases divided into two groups. The group I consisted of 60 patients with macroscopic hematuria, bladder carcinoma and malignant pelvic tumors after radiotherapy or operation. They underwent both IVU and MSCTU. The group II included 60 patients (≥ 40 years old) with retroperitoneal and malignant pelvic tumors, complicated pyelonephritis, microscopic hematuria, acute urinary tract obstruction (without visible calculi on unenhanced scans), and they were submitted to computed tomography with additional scan phase enabling MSCTU. Results. Compared with IVU, MSCTU is more sensitive for the detection of urinary tract diseases (parenchymal changes, renal tumors, urolithiasis, fibrosis) and extraurinary processes. MSCTU is more specific than IVU for renal parenchymal abnormalities, tumors of the excretory system, urolithiasis, bladder tumors, fibrosis and extraurinary diseases. MSCTU is equally sensitive, but more specific for hydronephrosis compared to MSCT. The diagnosis made by the use of MSCTU in patients with macroscopic and microscopic hematuria and with obstruction not caused by stones, perfectly comply with operative findings and histological diagnosis. Conclusion. The obtained results support MSCTU to be the modality of choice in the diagnostic algorithm of patients with macroscopic hematuria and in the evaluation of microscopic hematuria and unexplained obstruction of the urinary tract. The only remaining role for IVU in our institution is imaging of the upper urinary tract in patients with hematuria under the age of 40.